TEACHERâS COMPETENCE EXAMINATION (UKG) - ., Gunarto (MAGISTRA, 2013)
Gunarto. Teacherâs Competence Examination. This article is aimed to explain and giving the understanding to the readers especially to all teachers about UKG and PLPG includes the differences. The writer uses the document sources belongs to the government in this case, the Decision of Education Ministry, and UNS about the accomplishment and the manners about PLPG in district 113 at the year 2012, including the printed media Kompas. The difference between UKG and PLPG is UKG is so far used for knowing the teacherâs control their competence as a professional teacher, their remembering capability and their intelligence which is different for each teachers and their difference circumstances from the difference districts. The result of UKG is used to mapping and based of planning and to carry out the teacherâs erection so that they can set their selves as a professional teacher canât be used to stop their profession contribution. The UKG examination used on line and writing. The on line one the result can be known directly by the participants, while the PLPG Training is beginning with the tenth (10) days trainings (90 JP) ending with the writing test to know they passed or not, and carried out to get the education certificate and after that being a professional teacher and getting their professional contribution one time from the basic salary at the year they passed and getting their education certificate. The examination includes writing and practising right away guarded by the instructors. The decision of passing the exam is made by the Consortium of Sertificated Teachers (KSG) in Jakarta. The material which is examined includes pedagogy competence, professionalism, personality and social. Meanwhile the UKG examination which used the on line system, the material tested are pedagogy competence and professionalism. From the explanation above can be known clearly the understanding about PLPG and UKG includes the differentials. So that teachers can firmly placed theirselves in carrying out as a professional teacher. Keyword: pedagogy, professionalism, and competence.